2003
DOI: 10.4049/jimmunol.170.3.1374
|View full text |Cite
|
Sign up to set email alerts
|

Natural Substrates and Inhibitors of Mannan-Binding Lectin-Associated Serine Protease-1 and -2: A Study on Recombinant Catalytic Fragments

Abstract: Mannan-binding lectin-associated serine protease (SP) (MASP)-1 and MASP-2 are modular SP and form complexes with mannan-binding lectin, the recognition molecule of the lectin pathway of the complement system. To characterize the enzymatic properties of these proteases we expressed their catalytic region, the C-terminal three domains, in Escherichia coli. Both enzymes autoactivated and cleaved synthetic oligopeptide substrates. In a competing oligopeptide substrate library assay, MASP-1 showed extreme Arg selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
204
0
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(228 citation statements)
references
References 64 publications
9
204
0
8
Order By: Relevance
“…Three types of MASPs are associated in the proenzyme form with MBL: MASP-1, MASP-2, and MASP-3. The exact function of MASP-1 and MASP-3 has yet to be determined, although MASP-1 has been shown to cleave C3 weakly (12,13). MASP-2 has been shown to cleave C2 and C4 (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three types of MASPs are associated in the proenzyme form with MBL: MASP-1, MASP-2, and MASP-3. The exact function of MASP-1 and MASP-3 has yet to be determined, although MASP-1 has been shown to cleave C3 weakly (12,13). MASP-2 has been shown to cleave C2 and C4 (12)(13)(14).…”
mentioning
confidence: 99%
“…The exact function of MASP-1 and MASP-3 has yet to be determined, although MASP-1 has been shown to cleave C3 weakly (12,13). MASP-2 has been shown to cleave C2 and C4 (12)(13)(14). Binding of MBL⅐MASP complexes to sugar residues present on the cell surfaces of microorganisms results in a conformational change of MBL (15,16), which activates MASP-2.…”
mentioning
confidence: 99%
“…It was also suggested that MASP-1 can cleave C3, generating C3b before the assembly of the C3 convertase complexes (Matsushita et al, 2000). Detailed enzyme kinetic studies, however, revealed that although MASP-1 really cleaves C3, the catalytic efficiency (k cat /K M ) of this reaction is very low (3X10 2 M -1 s -1 ) (Ambrus et al, 2003) compared to the efficiency of a real C3 convertase, which is three orders of magnitude higher. This low C3…”
Section: The Mystery Surrounding the Role Of Masp-1mentioning
confidence: 99%
“…In contrast to MASP-1, MASP-2 has a partly occluded substrate binding cleft, and has only two major substrates -C2 and C4 (Ambrus et al, 2003). Therefore, it is not unexpected that MASP-2 does not cleave any PARs nor has any effects on endothelial cells (Megyeri et al, 2009).…”
Section: Only Masp-1 Activates Endothelial Cells Among Lectin Pathwaymentioning
confidence: 99%
See 1 more Smart Citation